Challenges and strategies in implementing 3D concrete printing (3DCP) technology in Malaysia: Materials and design codes - Siti Nur Natasha, Abdul Jalil; Ahmad Rizal, Alias; Aizat, Alias (IOP Publishing, 2025)
The rapid evolution of Malaysia's construction industry necessitates innovative solutions, and 3D Concrete Printing (3DCP) technology emerges as a transformative prospect. However, the successful integration of 3DCP faces numerous challenges, especially in the domains of materials and design codes. Thus, this research objective is to identify the challenges in implementing 3DCP technology in Malaysia construction industry from the perspective of materials and design codes and propose strategies for overcoming the identified challenges. The data collection involved individual interviews with expert industry practitioners involved with 3CDP technology in Malaysia. Then, the data is analyzed using the thematic analysis approach. The Dindings show that challenges identified were classified into three themes which are Input, Process and Output where some major challenges identified are high cost, lack of design standard and codes, unprepared industry and structural integrity. Meanwhile, internal and external strategies are proposed to overcome these challenges such as research and development, demonstration and promotions, industry engagement and expansion, collaboration and partnerships. The presented strategies aim to guide stakeholders in overcoming current challenges, facilitating a smoother integration of 3DCP technology and encouraging long-term advancements in the field.